2012
DOI: 10.1111/anae.12044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the single‐use Ambu® aScope™ 2 vs the conventional fibrescope for tracheal intubation in patients with cervical spine immobilisation by a semirigid collar*

Abstract: SummaryFibreoptic intubation remains a key technique for the management of difficult intubation. We randomly compared the second generation single-use Ambu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 18 publications
0
25
1
1
Order By: Relevance
“…The single‐use flexible bronchoscope (FB) represents a novel health technology. Several studies have demonstrated a clinical equivalence with its reusable counterpart in intubation success, time taken for intubation, picture quality, and ease of use . In addition, others have found that using reusable FBs can lead to cross‐contamination, highlighting one advantage of single‐use FBs in improved patient safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single‐use flexible bronchoscope (FB) represents a novel health technology. Several studies have demonstrated a clinical equivalence with its reusable counterpart in intubation success, time taken for intubation, picture quality, and ease of use . In addition, others have found that using reusable FBs can lead to cross‐contamination, highlighting one advantage of single‐use FBs in improved patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a clinical equivalence with its reusable counterpart in intubation success, time taken for intubation, picture quality, and ease of use. [8][9][10] In addition, others have found that using reusable FBs can lead to cross-contamination, 11,12 highlighting one advantage of single-use FBs in improved patient safety. As single-use FBs do not require any reprocessing, we hypothesized that they would also have strong organizational advantages at a hospital level.…”
mentioning
confidence: 99%
“…BAL, intubation, tracheotomy, biopsy and bronchial suction). Thus, this is a device comparable with a re-usable flexible bronchoscope in functionality, unlike other single-use devices without a working channel previously developed [9][10][11]. The results of this preliminary evaluation in animals and in the clinical setting demonstrate high satisfaction.…”
Section: Discussionmentioning
confidence: 82%
“…Although the performance of the device was acceptable, it was considered to be inferior to the usual flexible bronchoscope and disinfection was still required after use [7,8]. Other single-use devices have been developed for intubation or percutaneous tracheostomy, but the lack of an effective working channel was a major limiting factor [9][10][11]. An innovative single-use flexible bronchoscope with an internal working and suction channel of 2.0 mm diameter has recently been developed and is commercially available (Axess Vision Technology, Tours, France).…”
Section: Introductionmentioning
confidence: 99%
“…Piepho et al [6] studied the aScope™ and reported lower success rate for intubation and limited capacity to perform airway suctioning. Two additional drawbacks of the aScope™ are availability of only one size and its low image resolution [7, 8]. Mankikian found a global satisfaction with another type of single-use devices in clinical practice and for BAL in ventilated piglets [9].…”
Section: Introductionmentioning
confidence: 99%